Malaysia’s scholarly publishing ecosystem: An insider appraisal of established and emerging models - A. Abrizah,; M.M. Noor,; R. Abd-Shukor, (Malaysian Journal of Library and Information Science, 2025)
This article assesses Malaysia’s scholarly publishing ecosystem by analysing five models: university-based journals (UBJs), society journals, independent academic-led publishing initiatives, commercial partnership agreement, and ministry/government-sponsored journals. Drawing on over two decades of experience and the authors’ roles in national journal assessment, it examines the structural, ethical, and financial challenges shaping these models, particularly the tensions between Diamond and Gold Open Access frameworks. The findings indicate a system at a pivotal point, where commercial sustainability often conflicts with the principles of equitable knowledge dissemination. The authors argue that publishing models should be explicitly included as evaluation criteria in national frameworks, such as MyCite, to align with international practices. Recognising publisher credibility, governance, and financial transparency as core indicators of quality would help address existing legitimacy gaps. The article concludes with policy-oriented recommendations to reinforce community-controlled publishing, including the establishment of a National Council of Journal Editors. Such initiatives are vital to preserving Malaysia’s scholarly voice, values, and intellectual heritage within a balanced and globally connected knowledge infrastructure.